Evaluation Public Service Delivery in Azerbaijan: A Comprehensive Study of Challenges, Policy Alternatives, and Evaluation of ASAN service and E-Government Implementation - Ismayilov, Orkhan; Mustafayev, Shahriyar; Hummatzade, Khagan (ADA University, 2023)
It is very important to ensure efficiency and transparency in the provision of public services, to develop mechanisms for monitoring and complaining about public services, and to improve the efficiency and quality of public services. Public services are designed to enhance citizens' living conditions and solve their problems more efficiently and quickly. Public service evaluation is important for several reasons. It is essential for ensuring accountability, improving program outcomes, informing policy decisions, building public trust, and promoting a culture of learning and continuous improvement in government. The challenges, and propose solutions.
Keywords: Public administration -- Evaluation; Public services -- Quality control; Government accountability; Public and International Affairs